Environmental Performance Versus Corporate Financial Performance (Environemntal Media Exposure di Indonesia) - Rusli, Yohanes Mardinata (EQUITY, 2019)
The purpose of this study is examine the effect of environmental performance, type of industry and environmental media exposure on corporate financial performance in public companies listed on the Indonesia Stock Exchange during the period 2015-2017. The population used in this study are public companies or issuers other than financial service institutions or the banking and financial sectors listed on the Indonesia Stock Exchange. The data obtained is secondary data using library research. The sampling method used purposive sampling technique, obtained as many as 24 companies as a study sample for four years. The analysis in this study uses Statistical Product and Service Solutions (SPSS) software program version 24.0, where the statistical model used is multiple regression analysis. The results in this study are that environmental performance is good without and with the existence of moderating environmental media exposure variables having a significant and positive influence on corporate financial performance. While typr of industry is good without being moderated or moderating the variable environmental media exposure, it does not have a significant effect on corporate financial performance. For further research, it is recommended to enlarge the research sample not only limited to public companies or issuers other than financial service institutions, but also include public companies or issuers of the banking and financial sectors as research samples.